THE SULFONAMIDE EXPOSURE AND THE HISTOPATHOLOGICAL ALTERATIONS OF DOMESTIC PIGEON - Essa Isra; Al-Sereah Bahaa. A; Majeed Saleh. K; a. M (Basrah Journal of Veterinary Research)
A two months Toxicologicl pathology study of sulfonamide in domestic pigeons by oral intubation were done. The study was done at two dosage levels as intermediate 40mg/kg and high 80mg/kg with untreated control as third group. Clinical observation of treated birds did not show significant changes only the birds appeared to be quite after dosing for short time. Grossly, no obvious changes could be detected. Microscopically, Showed histopathological changes in pigeons represent of nephrotoxic effects characterized by degenerate and/or dilated cortical tubules in intermediate while, high dose groups appeared glomerular atrophy some with dilated Bowmans space, the severity of the changes were higher in the high dose group. In liver, peri portal and septal fibrosis in treated groups, some with parenchymal foci of inflammatory cell and vaculation of hepatocytes, while in pancreas, there was degenerate vacuolated islets of Langerhans in both treated groups, also in brain vacuolation of neurons and vacuoltion of nerve fiber in white matter of spinal cord. The severity of all above changes were higher in high dose than intermediate dose. Finally , the present study showed that domestic pigeons can tolerate varying toxic levels of sulfonamide with no mortality.